Teatro interculturale e corpi-in-relazione. AlmaTeatro e la questione dell'identità culturale oggi - Cristina Balma Tivola (Antropologia e Teatro, 2014)
Complex contemporary societies see the emergence upon the scene of realities and experiences whose individuals are from cultural or national origins other than Westerners. Whatever the practices adopted for the work, these realities always face the issues of cultural identity and diversity on stage as well as in their members everyday lives, and issues such as immigration, multiculturalism and interculturalism politics of the society where these experiences emerge and/or develop. The literature produced on the topic is already substantial, and present a huge number of cases. The most useful theoretical models to analyze these, their production processes and the networks of relationship they hold with the society they relate to are those by Gilbert & Lo and Holledge & Tompkins. The presentation of these models is accompanied here by their application in the analysis of the activity of a multi-and intercultural Italian theatre company, AlmaTeatro.